2021
DOI: 10.3390/molecules26133938
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk Triacylglycerol Regioisomer Ratio Shows Remarkable Inter-Breed and Inter-Cow Variation

Abstract: Regioisomers (or positional isomers) of triacylglycerols (TAGs) of milk are known to show differential outcome in relation to human absorption. Quantitation of TAG regioisomers remains a big challenge due to the lack of facile chromatographic separation technique. The feasibility of using fragment ion intensity ratio to determine the ratio of co-eluting AAB/ABA-type regioisomer pairs was confirmed in this study. The ability of C30 stationary phase in resolving interfering TAG isomers was demonstrated for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The method was applied for analyzing the OPO/OOP and the OSO/OOS pairs using fragment ion intensity ratios. As a result, it provides structural information for targeted TAGs rather than comprehensive information on the regioisomer profile in bovine milk . They concluded that the regioisomer ratios are affected by both cow breed and individual cows, but our OPO and OSO ratios are comparable with the average results in their study, having the closest matching profile of the two regioisomer pairs in the milk fat of the Jersey cow breed.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The method was applied for analyzing the OPO/OOP and the OSO/OOS pairs using fragment ion intensity ratios. As a result, it provides structural information for targeted TAGs rather than comprehensive information on the regioisomer profile in bovine milk . They concluded that the regioisomer ratios are affected by both cow breed and individual cows, but our OPO and OSO ratios are comparable with the average results in their study, having the closest matching profile of the two regioisomer pairs in the milk fat of the Jersey cow breed.…”
Section: Resultssupporting
confidence: 88%
“…For comparison of the bovine milk TAG regioisomer results, there are very limited studies that have taken into account the effects of isobaric fragment ion interference. Recently, Liu et al demonstrated the regioisomeric analysis of specific bovine milk TAGs emphasizing chromatographic separation of interfering isobaric TAGs species with C30 stationary phase column . The method was applied for analyzing the OPO/OOP and the OSO/OOS pairs using fragment ion intensity ratios.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trên thế giới đã có nhiều phương pháp xác định hàm lượng OPO trong chất béo, trong thịt lợn, thịt bò và sữa, bằng nhiều kỹ thuật như sắc ký khí ion hóa ngọn lửa GC-FID [4][5], quang phổ cộng hưởng từ hạt nhân 13 C-NMR [6], sắc ký lỏng và sắc ký lỏng khối phổ [7][8][9]. Tuy nhiên, phương pháp GC-FID có quá trình xử lý mẫu phức tạp, tốn nhiều thời gian.…”
Section: Hình 1 Công Thức Cấu Tạo Của 13-olein-2-palmitin (Opo)unclassified